Poética do encantamento: a voz da criança em João Guimarães Rosa - Leite, Paloma da Silveira (2019)
This dissertation deals with the magical universe of childhood in João Guimarães Rosa, more specifically the short stories Partida do audaz navegante (1962) and Fita verde no cabelo (1970), and the novella Campo Geral (1964). In a context in which the child rarely has its own voice, Rosa, specially for having the ―childhood feeling‖, shows us magical minds, that allow themselves to live in the universe of the imaginary, bordering the nonsensical. More than that, there are signs and clues about the turning point attributed to rites of passage, that definitive moment which separates childhood from adulthood. Theoretical foundation is based on theories of the wonderful of Todorov, Mieletinski e Propp, theories of the imaginary of Bachelard, Mielietinskyamong others. We will also consider Walter Benjamin to think about Literature and childhood. The critical fortune about the author is sustained in the voice of Henriqueta Lisboa, Benedito Nunes, Paulo Rónai. The study showed, among other considerations, that Rosa, instead of reproducing a child‘s thoughts keeping a safe distance from infantile imaginary, dilutes his discourse and his poetic outlook into those of the narrators and characters, mingling almost inseparably his own discourse into the child‘s, building a magical-poetical idea in in a poetical-wonderful world